IL-17A inhibitors modulate skin microbiome in psoriasis: implications for microbial homeostasis - Ying Lv; Huiying Bian; Yanjia Jing; Jing Zhou (Journal of Translational Medicine)
Abstract Background The IL-17A inhibitors target aberrant immune responses in psoriasis but also impacts the host’s defense against infections. The effects of this treatment on skin microorganisms and microbiome-encoded metabolic pathways remain unclear. Objectives This was an exploratory clinical study designed to investigate whether Psoriasis is associated with skin microbiota, as well as a longitudinal cohort study aimed at revealing the effects of IL-17A inhibitor treatment on skin microbiota in Psoriasis. Methods In this study, we recruited 26 patients with moderate to severe psoriasis and 15 healthy controls. We collected skin microbiome samples from both greasy and dry skin regions. All samples were analyzed using 16S rDNA gene sequencing to determine the microbial profiles. Results Compared with healthy controls, the composition and function of skin microbiome in psoriasis patients are heterogeneous. Treatment with IL-17A inhibitors significantly increases the alpha diversity of the skin microbiota in psoriasis patients, indicating potential restoration of microbial community richness and evenness. However, this treatment does not entirely alter the taxonomic composition of the skin microbiota; rather, it shifts the relative abundance of specific microbial species, indicating that certain core microbial features remain relatively stable. Moreover, IL-17A inhibitors help adjust the functional profile of the skin microbiome in psoriasis patients, bringing it closer to that of healthy individuals. Conclusions Psoriasis patients exhibit significant heterogeneity in both the composition and functionality of their skin microbiota. Although IL-17A inhibitor treatment fails to fundamentally alter its taxonomic composition, this therapy effectively enhances microbial community stability by increasing alpha diversity and modulating the relative abundance of various taxa. Additionally, it adjusts the functional profile of the skin microbiota towards a healthier state, thereby contributing to the restoration of microecological balance.